Interpretation and revision of international boundary decisions - Kaikobad, Kaiyan Homi (Cambridge Cambridge University Press, 2007)
This book, first published in 2007, seeks to examine a consistent theme occurring in judgements and awards given by international tribunals in the matter of boundary disputes, a theme which is predicated on finding some sort of difficulty in the implementation of those awards and judgements. This is a feature prominent in boundary and territorial disputes inasmuch as decisions relative to title to territory and location of a boundary line are always keenly contested and hotly disputed. Two remedies which have frequently been relied on by States are those of interpretation and revision. The author sheds light on how, when and in what circumstances will the tribunal be able to interpret or revise either its own or another tribunal's decisions. By doing so, the study succeeds in contributing to an understanding of this area of the law.
Electronic reproduction.
Keywords: Boundary disputes; Electronic books